Improving equity and wellness in cancer care with people of Latin American and African Descent: a study protocol - Santos Salas, Anna; Watanabe, Sharon M.; Sinnarajah, Aynharan; Bassah, Nahyeni; Huang, Fleur; Alcalde-Castro, Jacqueline; Judge, Harkeert; O'Rourke, Hannah M.; Camargo Plazas, Pilar; Salami, Bukola; Santana, María J.; Abdel Rahman, Omar; et al. (Frontiers in Oncology, 2025)
BackgroundCancer inequities such as late access to cancer screening and diagnosis affect people of African and Latin American descent in Canada. These inequities in addition to experiences of racism and discrimination and unequal living and working conditions are detrimental to their wellness. We aim to delineate together with people of African and Latin American descent a patient-oriented pathway to improve their equity and wellness in cancer care.MethodsThis is a 3-year community-based and patient-oriented participatory research study. The study will take place in Alberta and Ontario and will involve 125 participants including people with cancer, family and community members of African and Latin American descent, and health care providers. We will conduct in-depth interviews with patients and families and focus groups with community members. Together with patient partners and community collaborators, we will delineate a patient-oriented pathway in cancer care to improve equity and wellness for people of African and Latin American descent in Canada. Finally, we will explore the acceptability of the pathway with a small sample of patients, families and health care providers.ConclusionThis study will advance our knowledge of equity and wellness in people with advanced cancer from racialized communities in Canada; and increase our understanding of how racialized populations live through a cancer diagnosis. The study will also generate knowledge of how a patient-oriented health equity pathway can contribute to reduce cancer inequities in the care of our study populations.